2006
DOI: 10.1161/01.atv.0000222011.13026.25
|View full text |Cite
|
Sign up to set email alerts
|

Common Genetic Variation in Five Thrombosis Genes and Relations to Plasma Hemostatic Protein Level and Cardiovascular Disease Risk

Abstract: Objective-We undertook a linkage disequilibrium (LD)-based genetic approach to investigate the hypothesis that common sequence variants in 5 thrombosis genes influence plasma hemostatic protein levels or risk of cardiovascular disease (CVD). Methods and Results-In a reference panel, we characterized LD structure at the fibrinogen gene cluster (fibrinogen-␤[FGB], FGA, and FGG), factor VII (F7), and tissue plasminogen activator (PLAT) loci. Forty-one tag single nucleotide polymorphisms (SNPs) were genotyped in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
39
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 38 publications
12
39
1
1
Order By: Relevance
“…In line with this hypothesis, it has been found that subjects carrying a variant of the t-PA gene with a low capacity for t-PA release are at greater risk of suffering a MI [4,5]. This finding was recently reproduced in the Framingham cohort [6]. A reduced capacity to release t-PA has also been observed in subjects with an increased risk of myocardial infarction, i.e.…”
Section: Introductionmentioning
confidence: 84%
“…In line with this hypothesis, it has been found that subjects carrying a variant of the t-PA gene with a low capacity for t-PA release are at greater risk of suffering a MI [4,5]. This finding was recently reproduced in the Framingham cohort [6]. A reduced capacity to release t-PA has also been observed in subjects with an increased risk of myocardial infarction, i.e.…”
Section: Introductionmentioning
confidence: 84%
“…Fibrinogen gene variation and ischemic stroke 901 associated with increased plasma fibrinogen level [20][21][22]30]. The effect was modest and only present in cases.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicate that the FGA and FGG genes may be of importance [13,14]. In contrast, several studies have investigated the possible association between fibrinogen gene polymorphisms, plasma fibrinogen level, and ischemic stroke, as well as coronary heart disease [15][16][17][18][19][20][21][22]. Although many studies have reported an association between FGB gene polymorphism and plasma fibrinogen, results have been inconsistent with respect to cardiovascular and cerebrovascular events [22].…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress in genomics, such as the International HapMap Project [International HapMap Consortium, 2005] allows the comprehensive study of common sequence variation at a gene locus, and the identification of blocks of linkage disequilibrium (LD) for neighboring SNPs. In the fibrinogen gene cluster, 44 SNPs spanning a genomic region of 61.8 kb were found to fall into three LD blocks, with four to six haplotypes for each block, representing more than 95% of chromosomes [Kathiresan et al, 2006].…”
Section: Polymorphismsmentioning
confidence: 99%